1999
DOI: 10.1074/jbc.274.51.36058
|View full text |Cite
|
Sign up to set email alerts
|

The Role of External Loop Regions in Serotonin Transport

Abstract: Chimeric transporters were constructed in which the predicted external loops of the serotonin transporter (SERT) were replaced one at a time with a corresponding sequence from the norepinephrine transporter (NET). All of the chimeric transporters were expressed at levels equal to or greater than those of wild type SERT, but the transport and binding activity of the mutants varied greatly. In particular, mutants in which the NET sequence replaced external loops 4 or 6 of SERT had transport activity 5% or less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…This process turns the outward-facing form of the protein, in which residue 223 is externally exposed, into the inward-facing form, where this residue is occluded from the external medium. Although a relevant role in substrate or inhibitor binding has been reported for hydrophilic loops in the ␥-aminobutyric acid transporters (54), it has also been recently suggested that the complementary functions of binding and conformational changes in the transport cycle are subserved by the transmembrane and loop domains, respectively (55). Our results may also reinforce this hypothesis.…”
Section: Figsupporting
confidence: 81%
“…This process turns the outward-facing form of the protein, in which residue 223 is externally exposed, into the inward-facing form, where this residue is occluded from the external medium. Although a relevant role in substrate or inhibitor binding has been reported for hydrophilic loops in the ␥-aminobutyric acid transporters (54), it has also been recently suggested that the complementary functions of binding and conformational changes in the transport cycle are subserved by the transmembrane and loop domains, respectively (55). Our results may also reinforce this hypothesis.…”
Section: Figsupporting
confidence: 81%
“…Evidence from external loop chimeras suggests that these loops are important for the conformational changes that follow binding (22). It is conceivable that the structural basis for our observations lies in the conformational changes in the first external loop, which contains Cys-109, that accompany ligand and ion binding to SERT.…”
Section: Discussionmentioning
confidence: 77%
“…We cannot at present exclude the possibility that incorporation of the ligand occurs in loop structures but will focus on the transmembrane spanning sequence as the likely site of attachment, because most currently available evidence indicates that determinants for uptake blocker binding in DAT and related transporters are present in TMs rather than in loops (21,22 (27), whereas increased cocaine affinity occurred at D313N (26). Most of the inhibitory mutations decreased cocaine affinity by only modest amounts (2-to 3-fold) that may be consistent with indirect effects on binding site structure rather than alteration of direct interaction sites, although mutation of multiple contact points may be required to reduce inhibitor affinity more significantly (28 (6).…”
Section: Discussionmentioning
confidence: 99%